Acute Liver Failure in Dengue: A Common but Overlooked Entity in Pediatric Patients in Tropical Countries. Issue 2 (27th October 2022) - Dogra, Surabhi; Kumar, Karunesh; Malhotra, Smita; Jerath, Nameet; Sibal, Anupam
Abstract : Objective: The objective of the study is to estimate the incidence of acute liver failure (ALF) in dengue infection, understand the demographic and biochemical profiles, and identify prognostic factors associated with mortality. Methodology: This is a retrospective observational study. We evaluated the data of all pediatric dengue patients admitted over the last 5 years in our hospital to identify patients who fulfilled the criteria for pediatric ALF. Demographic profile, and biochemical and radiological parameters were assessed. Their outcomes and mortality data were analyzed to identify prognostic factors. Results: Thirty children with dengue infection were identified to have developed a during the ALF study period which was 29.1% (30 of 103) of all our ALF admissions. A total of 189 children with dengue infection needed admission during the same period and 15.8% (30 of 189) of them developed ALF. The mean duration of onset of ALF was 5.4 days after fever onset. Twenty-two patients (73%) survived, and 8 patients expired. High creatinine, low albumin level, and multisystemic involvement were identified as poor prognostic markers in those patients who did not survive. Conclusion: ALF is common in admitted severe dengue patients. A significant proportion of acute liver patients in endemic countries can be attributed to dengue infection. Low serum albumin, high creatinine, and multi-organ dysfunction during acute illness can be used as prognostic markers in these children. Multicentric prospective studies are needed to validate these results.